High ambient temperatures and ethology of bees - Brovarskyi , Valerii; Brindza, Jan; Turdaliev, Avazbek Turdalievich; Mirzakhmedova, Hiulkhaio; Velychko, Oleksandr (Problems of Environmental Biotechnology, 2021)
The influence of high temperatures on the efficiency of nectar secretion by plants in different ecosystems has been studied. The attractiveness of flowers of agricultural crops and wild plants for bees has been determined. The ethology of flying bees and the reaction of families under the action of different ambient temperatures are analyzed.